2012
DOI: 10.1093/humrep/27.s2.73
|View full text |Cite
|
Sign up to set email alerts
|

Andrology

Abstract: Introduction:In the last decades sperm DNA quality has been recognized as one of the most important markers of male reproductive potential (Lewis and Aitken, 2005; Ozmen, 2007; Tarozzi, 2007), in contrast to standard semen parameters as sperm density, motility and morphology, which do not act as powerful discriminators between fertile and infertile men. DNA damage in the male germ line is a major contributor to infertility, miscarriage and birth defects in the offspring. In animal models, it has been unequivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…MACS is an efficient method that can avoid apoptotic sperm during selection. MACS efficiently reduces sperm DNA fragmentation levels [13,19,29,30,40,47,48] and effectively separates apoptotic from non-apoptotic spermatozoa [6, 8, 11, 14, 17-20, 28, 29, 34, 37-39, 44]. This selection leads to an improvement in sperm quality and functionality [14,19,23] because MACS positively affects sperm motility [5,8,29,34,38,41] and morphology as determined by the sperm deformity index [2-4, 38, 39, 41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MACS is an efficient method that can avoid apoptotic sperm during selection. MACS efficiently reduces sperm DNA fragmentation levels [13,19,29,30,40,47,48] and effectively separates apoptotic from non-apoptotic spermatozoa [6, 8, 11, 14, 17-20, 28, 29, 34, 37-39, 44]. This selection leads to an improvement in sperm quality and functionality [14,19,23] because MACS positively affects sperm motility [5,8,29,34,38,41] and morphology as determined by the sperm deformity index [2-4, 38, 39, 41].…”
Section: Discussionmentioning
confidence: 99%
“…MACS efficiently reduces sperm DNA fragmentation levels [13,19,29,30,40,47,48] and effectively separates apoptotic from non-apoptotic spermatozoa [6, 8, 11, 14, 17-20, 28, 29, 34, 37-39, 44]. This selection leads to an improvement in sperm quality and functionality [14,19,23] because MACS positively affects sperm motility [5,8,29,34,38,41] and morphology as determined by the sperm deformity index [2-4, 38, 39, 41]. Several authors reported an improvement in fertilization rates [12,36] and embryo quality [1,9,40] because the best sperms were selected using MACS compared with standard selection methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advancement of technology, various ART treatments were applied on CHH patients in different situations such as age, sex, region, duration and extent of illness. The success rate increased to 55% [ 14 , 15 ]. Furthermore, a study in 1997 first emphasized that initiation of ICSI treatment after testicular maturity induced by hormonal treatment contributed to the success of ART [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature estimates that male infertility accounts for 30% to 40% of infertility among couples (1)(2)(3). Before fertility treatments can be initiated, it remains unclear on what should be the optimal period of sexual self-restraint required to warrant maximum quality sperm is achieved.…”
Section: Introductionmentioning
confidence: 99%